1991
DOI: 10.1055/s-2006-960105
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Evaluation of Possible Teratogenic Potential inBoerhaavia diffusain Albino Rats

Abstract: The present study was undertaken to evaluate any possibility of teratogenic effects in Boerhaavia diffusa (Punarnava), a widely used herbal medicine for renal and urinary tract diseases by Ayurvedic physicians in India. The ethanolic extract of Boerhaavia diffusa (BDE) was administered daily in a dose of 250 mg/kg, body weight p.o., to pregnant albino female rats during the entire period of gestation. BDE was found to be devoid of any teratogenic effect as litter size and survival rate of foetuses were the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It was tested for the presence of alkaloids. In a previous study the extract does not showed any sign of toxicity up to an oral dose of 2g/Kg in mice (Chandan et al, 1991), and an oral administration of 250mg/Kg to pregnant Albino rats during the entire gestation period was found to be devoid of any teratogenic effect (Sing et al, 1991). Hence the concentration used in this study (25mg/Kg, route i.p.)…”
Section: Extract Preparationmentioning
confidence: 75%
“…It was tested for the presence of alkaloids. In a previous study the extract does not showed any sign of toxicity up to an oral dose of 2g/Kg in mice (Chandan et al, 1991), and an oral administration of 250mg/Kg to pregnant Albino rats during the entire gestation period was found to be devoid of any teratogenic effect (Sing et al, 1991). Hence the concentration used in this study (25mg/Kg, route i.p.)…”
Section: Extract Preparationmentioning
confidence: 75%
“…An assessment of the ethanol extract showed no increase in cellular volume and protein content in H9C2 cells . The safety of extracts has also been observed in vivo …”
Section: Discussionmentioning
confidence: 91%
“…[17] The safety of extracts has also been observed in vivo. [38,39] Reactive oxygen species have been identified as one of the key players in the maintenance of cellular physiology by regulating diverse downstream signalling pathways leading to specific functions such as cellular division, growth, apoptosis and necrosis. [8,40,41] However, excessive generation of ROS may result in cellular deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…It is antibacterial, antioxidant and antidiabetic. It contains arachidic acid, behenic acid, saturated fatty acids, vitamins C, lignin, phenolics, steroids, glycosides and boeravinone B …”
Section: Management Of Utimentioning
confidence: 99%